Intraoperative Core Temperature Patterns, Transfusion Requirement, and Hospital Duration in Patients Warmed With Forced Air. Issue 3 (June 2016) - Sun, Zhuo; Honar, Hooman; Sessler, Daniel I.; Dalton, Jarrod E.; Yang, Dongsheng; Panjasawatwong, Krit; Deroee, Armin F.; Salmasi, Vafi; Saager, Leif; Kurz, Andrea
Abstract : (Abstracted from Anesthesiology, 122:276–285, 2015) Intraoperative core hypothermia can expose a patient to multiple complications. It is common for patients' core body temperature to be warmed through a forced air approach, but the core body temperature patterns with this method have been poorly characterized.